Prevention of SIVmac251 reservoir seeding in rhesus monkeys by early antiretroviral therapy - James B. Whitney (Nature Portfolio, 2018)
The latent HIV-1 reservoir is the key obstacle for curing HIV-1 infection, but the timepoint at which the HIV-1 reservoir is established is currently unclear. Here, Whitney et al. show in non-human primates that the SIV reservoir in CD4+ T cells is seeded within the first 2 days after infection.